2003
DOI: 10.1152/ajpheart.00885.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy vector-mediated expression of insulin-like growth factors protects cardiomyocytes from apoptosis and enhances neovascularization

Abstract: therapy vectormediated expression of insulin-like growth factors protects cardiomyocytes from apoptosis and enhances neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…27,29,41 The most important difference between HB-EGF and HGF/IGF, which accounts for the observed discrepancy, is the lack of a direct cytoprotective effect of HB-EGF on cardiomyocytes, in contrast to the potent cytoprotective effect observed for HGF and IGF in injured hearts. 27,29,41 This is a unique feature of HB-EGF, because most organogenic and/or organotrophic growth factors exert direct antiapoptotic effects, for example, HGF or IGF in mouse or rat cardiomyocytes [26][27][28][29] and HB-EGF in the small intestine. 42 In this regard, future studies to explore the differences among the molecules and signal transduction pathways involved in the activity of each growth factor would be biologically important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27,29,41 The most important difference between HB-EGF and HGF/IGF, which accounts for the observed discrepancy, is the lack of a direct cytoprotective effect of HB-EGF on cardiomyocytes, in contrast to the potent cytoprotective effect observed for HGF and IGF in injured hearts. 27,29,41 This is a unique feature of HB-EGF, because most organogenic and/or organotrophic growth factors exert direct antiapoptotic effects, for example, HGF or IGF in mouse or rat cardiomyocytes [26][27][28][29] and HB-EGF in the small intestine. 42 In this regard, future studies to explore the differences among the molecules and signal transduction pathways involved in the activity of each growth factor would be biologically important.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that improvement of cardiac dysfunction after MI has been successfully achieved by gene therapy using angiogenic factors that do not directly act on cardiomyocytes. 29,43 This fact suggests that angiogenesis plays a crucial role in postinfarction remodeling, and that the absence of an angiogenic effect of overexpressed HB-EGF may be largely responsible for its lack of therapeutic action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter examined cytokine responses to SDF-1 delivery in a synthetic scaffold; however, our results also suggest that the SDF-1 microsphere matrix supports a favourable environment for angiogenic activity through local factors, as evidenced by increased IGF-1 and VCAM-1 in hindlimb lysates. IGF-1 is a stimulator of angiogenesis (Su et al, 2003) and is cytoprotective (Li et al, 1997), and elevated IGF-1 is ideal for recovery. Pelosi et al (2007) have shown that persistent IGF-1 expression accelerates the regenerative response and restores architecture and structure soon after skeletal muscle injury.…”
Section: Kuraitis Et Al Controlled Sdf-1 Release For Treating Ischmentioning
confidence: 99%